2021
DOI: 10.1101/2021.02.05.21251219
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The antibody response to SARS-CoV-2 infection persists over at least 8 months in symptomatic patients

Abstract: The factors involved in the persistence of antibodies to SARS-CoV-2 are unknown. We evaluated the antibody response to SARS-CoV-2 in personnel from 10 healthcare facilities and its association with individuals' characteristics and COVID-19 symptoms in an observational study. We enrolled 4735 subjects (corresponding to 80% of all personnel) over a period of 5 months when the spreading of the virus was drastically reduced. For each participant, we determined the rate of antibody increase or decrease over time in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(31 reference statements)
1
1
1
Order By: Relevance
“…The second multivariate LR analysis after the second vaccine dose (which was set at 21 days) also showed a good prediction of the actual IgG amount after the second dose (R 2 = 0.67, F-statis- an increase of antibodies in the natural infection (11). Here, we found that anosmia/dysgeusia correlated with increased IgG after the second dose of vaccine (P = 0.01).…”
Section: Funding Dolce and Gabbana And The Italian Ministry Of Health (Ricerca Corrente)supporting
confidence: 67%
“…The second multivariate LR analysis after the second vaccine dose (which was set at 21 days) also showed a good prediction of the actual IgG amount after the second dose (R 2 = 0.67, F-statis- an increase of antibodies in the natural infection (11). Here, we found that anosmia/dysgeusia correlated with increased IgG after the second dose of vaccine (P = 0.01).…”
Section: Funding Dolce and Gabbana And The Italian Ministry Of Health (Ricerca Corrente)supporting
confidence: 67%
“…These results contrast with our previous report indicating that patients with prolonged anosmia had lower levels of nasal, but not serum IgG, 2 months after onset of symptoms 7 . This difference suggests that anosmia is associated with dynamic changes in antibody levels that may be related to the changes in SARS‐CoV‐2 antigen load 16 . The association with serum and nasal IgG, and not IgA, levels suggests that antigen challenge occurs at the systemic level.…”
Section: Resultscontrasting
confidence: 91%
“…We recently reported in a longitudinal seroprevalence study conducted in a cohort of working adults ( n = 1,655) that SARS-CoV-2 RBD-specific antibodies (Abs) persist for at least 6 months independent of symptom severity; we further observed that COVID-19 symptoms anosmia and/or dysgeusia correlated most closely with the detection of virus-neutralizing Abs ( 1 ). Also others have shown that COVID-19 symptom severity and in particular loss of taste and/or smell were associated with induction of higher Ab levels which persisted for up to 8 months after infection ( 2 4 ). In order to assess SARS-CoV-2 seroprevalence in the investigated cohort at the end of the third pandemic wave in Austria and to determine Ab persistence over 1 year, the study subjects were invited to a follow up blood draw between mid-April and mid May 2021.…”
Section: Introductionmentioning
confidence: 93%